The relationship between sample size and its suitability for exploratory factor analysis in cognitive abilities test (Journal of the College of Basic Education, 2022)
The current study aims to know the nature of the relationship between the sample size and each of the indicators of the appropriateness of the sample size in the exploratory factor analysis. - Al-Mustansiriya University, random samples were drawn, and the data was processed by the SPSS 21 program,Indicators of the suitability of the sample size were calculated for each of the research samples. An exploratory factor analysis was conducted by the method of the main components and the subscriptions were calculated, and the results concluded the following: All indicators of suitability were good and acceptable for all research samples, and the most suitable of them was with the sample 100 with the highest subscriptions among the samples. The research, as it was found that there is a weak negative relationship between sample size and indicators of suitability: MAS test (-0.31) and Keiser-Mayer-Olkin test (-0.27) and there is no relationship between sample size with MAS index, and the relationship between sample size and determinant of the correlation matrix was positive and strong (0.77) .